How do women want to receive information about non‐invasive prenatal testing? Evidence from a discrete choice experiment. (2nd October 2022) - Wright, Stuart J.; Dalal, Garima; Vass, Caroline M.; Georgsson, Susanne; Payne, Katherine
Abstract: Objective: Non‐invasive prenatal testing (NIPT) identifies the risk of abnormalities in pregnancy, potentially reducing the risk of miscarriage associated with invasive tests. This study aimed to understand the preferences of current and future mothers about the content, format and timing of information provision about NIPT. Methods: An online discrete choice experiment was designed comprising four attributes: when in the pregnancy information is provided (4 levels); degree of detail (2 levels); information format (6 levels); cost to women for gathering information (5 levels). Respondents included women identified by an online‐panel company in Sweden. The mathematical design was informed by D‐efficient criteria. Choice data were analysed using uncorrelated random parameters logit and latent class models. Results: One thousand Swedish women (56% current mothers) aged 18–45 years completed the survey. On average, women preferred extensive information provided at/before 9 weeks of pregnancy. There was heterogeneity in preferences about the desired format of information provision (website, mobile app or individual discussion with a midwife) in the population. Conclusion: Women had clear preferences about the desired content, format and timing of information provision about NIPT. It is important to tailor information provision to enable informed choices about NIPT. Key points: What's already known about the topic? Non‐invasive prenatal testing (NIPT) is an emerging approach that detects fetal DNA from a maternal blood sample to identify the risk of abnormalities in pregnancy. Parents must be given the correct type and amount of information in an appropriate format. The information is needed to provide consent for undergoing NIPT. What does the study add? A discrete choice experiment was used to quantify the preferences of current and future mothers for content, format and timing of the provision of information about NIPT. Women had a strong preference for extensive information provided early in pregnancy using a variety of formats (text‐based websites; mobile apps; individual discussions with a midwife). Substantial heterogeneity in preferences was identified suggesting a tailored approach to effectively provide information about NIPT is required.